INSECTICIDE RESISTANCE IN MOSQUITO VECTORS IN NIGERIA: A GEOSPATIAL REVIEW OF PUBLISHED EVIDENCE - Adeogun, Adedapo O.; Babalola, Ayodele S.; Babatunde, Taiwo P.; Oyelude, Funmilola Janet; Fawole, Jumoke; Adediran, Adewale; Olagundoye, Olalekan; Busari, Lateef; Adesoye, Oluwaseun Adegbola; Adeleke, Monsuru A.; Idowu, Olufunmilayo A. (FUDMA JOURNAL OF SCIENCES, 2025)
Insecticide resistance among mosquito vectors poses a significant threat to the sustainability of malaria control and other vector-borne disease elimination programs. This study systematically collated and analyzed published data on insecticide resistance monitoring in Nigeria from 2007 to 2025, covering 54 studies across 180 unique locations. Data were synthesized to examine temporal trends, geospatial distribution, and resistance mechanisms across mosquito genera and four major insecticide classes. The findings reveal widespread resistance across Nigeria, with pyrethroids—the cornerstone of long-lasting insecticidal nets (LLINs)—being the most frequently tested and most resisted class. Pockets of susceptibility to pyrethroids were observed in limited areas of southern Nigeria (Lagos, Ondo, and Delta States). Resistance to carbamates, organochlorines, and organophosphates was also documented, though organophosphates were the least studied. Genus-specific analysis demonstrated that Anopheles, Culex, and Aedes mosquitoes all exhibited resistance, with Anopheles showing the broadest geographic spread. Mechanistic data highlighted a predominant role of metabolic resistance, often occurring alone or in combination with knockdown resistance (kdr) mutations, although kdr mutations were particularly notable in Culex populations and in selected Anopheles populations in southwestern and northeastern regions. These findings underscore the urgent need to strengthen insecticide resistance surveillance and integrate resistance management strategies into malaria control programs in Nigeria. The widespread loss of susceptibility to pyrethroids highlights the importance of transitioning to next-generation vector control tools, diversifying insecticide use, and investing in novel interventions. Continuous monitoring and operational research are critical to inform evidence-based vector control policies and safeguard public health gains.